2020
DOI: 10.3390/jcm9082632
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Type 2 Diabetes Mellitus on the Hypoxia-Inducible Factor 1-Alpha Expression. Is There a Relationship with the Clock Genes?

Abstract: Limited reports exist on the relationships between regulation of oxygen homeostasis and circadian clock genes in type 2 diabetes. We examined whether the expression of Hypoxia-Inducible Factor-1α (HIF-1α) and HIF-2α relates to changes in the expression of clock genes (Period homolog proteins (PER)1, PER2, PER3, Retinoid-related orphan receptor alpha (RORA), Aryl hydrocarbon receptor nuclear translocator-like protein 1 (ARNTL), Circadian locomotor output cycles kaput (CLOCK), and Cryptochrome proteins (CRY) 1 a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
10
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(12 citation statements)
references
References 38 publications
1
10
0
1
Order By: Relevance
“…All the protein levels were measured using ELISA assay. Similar outcomes were obtained among diabetes mellitus type 2 patients [ 46 ], patients with hepatocellular carcinoma [ 34 ], or varicose lesions [ 47 ]. However, early reports suggest that one-night effective continuous positive airway pressure (CPAP) treatment does not affect the level of HIF-1α in OSA patients [ 48 , 49 ].…”
Section: Possible Molecular Mechanisms In Osasupporting
confidence: 60%
See 1 more Smart Citation
“…All the protein levels were measured using ELISA assay. Similar outcomes were obtained among diabetes mellitus type 2 patients [ 46 ], patients with hepatocellular carcinoma [ 34 ], or varicose lesions [ 47 ]. However, early reports suggest that one-night effective continuous positive airway pressure (CPAP) treatment does not affect the level of HIF-1α in OSA patients [ 48 , 49 ].…”
Section: Possible Molecular Mechanisms In Osasupporting
confidence: 60%
“…In an evolutionary sense, it increases energetic efficiency [ 59 ]. The disruption of its function may lead to diabetes mellitus type 2 (T2DM), dyslipidemia, obesity, and metabolic syndrome [ 46 , 67 , 68 , 69 ].…”
Section: Clinical Implications Of Circadian Rhythm Gene Disruption In Osa Patientsmentioning
confidence: 99%
“…Lactic acid is an important product of glucose metabolism exerting metabolic and non-metabolic functions. Plasma lactate concentration is highest in obese subjects with type 2 diabetes mellitus (T2DM), which is associated with both fasting plasma glucose and glycated haemoglobin concentrations (Y. D. Chen, Varasteh, & Reaven, 1993), and recent studies confirm the results and such a relationship (Higuchi et al, 2020;Lopez-Cano et al, 2020). Moreover, lactates are increased in kidney and urine of T1DM rats (Zhao et al, 2011).…”
Section: Introductionmentioning
confidence: 93%
“…Li et al, 2008;Yamaguchi et al, 2009). Anaerobic glycolysis and its product lactate are the major energy source of podocytes (Brinkkoetter et al, 2019;Ozawa et al, 2015), and lactate levels are elevated in blood and kidney in diabetic conditions (Y. D. Chen et al, 1993;Higuchi et al, 2020;Lopez-Cano et al, 2020;Zhao et al, 2011). Based on these reports, in the current study, firstly we found that lactate levels were increased in high glucose-stimulated mouse podocytes as well as blood and kidney of diabetic mice, which possibly was due to the upregulated MCT2 in mitochondria and the decreased PDH activity.…”
Section: Lactate-lowering Differently Affected Mct2 and Mct4 Expressi...mentioning
confidence: 99%
“…Some experiments had shown that the activation of HIF-1α could control the weight and blood glucose of the model mice, the insulin sensitivity, lipid metabolism level and albuminuria of the model mice were improved, which might suggest that HIF-1 signaling pathway has a potential impact on diabetes and its complications [32]. Some studies found that HIF-1α gene expression in T2DM patients with poor metabolic control was decreased [33]. However, some studies showed that the level of HIF-1α in T2DM patients was signi cantly higher than that in the control group, and insulin secretion increased when hypoxia was inhibited [34].…”
Section: Component-target Molecule Docking Of Dhxdmentioning
confidence: 99%